Media representation of people with disabilities (OKU) / Ireena Nasiha Ibnu ... [et al.] - Ibnu, Ireena Nasiha; Hairil Yahri, Nurin Sofiya; Azian, Nordiyanah Munirah; Mohd Azman, Mohd Danial; Jaafar, Qurratu'Aini (Faculty of Communication & Media Studies, 2021)
This research study examined the impact of marginalised groups, particularly people with disabilities, otherwise known as 'Orang Kurang Upaya' (OKU) and their representation in Malaysian media. A structured survey questionnaire was conducted for data collection to identify public perception and attitude towards the members of the disabled community. This paper focused on the depiction of OKU in visual media, primarily television and films in Malaysia. Overall, the report laid out that portrayal of disability in Malaysian media is correlated to individuals belief and perception exposed in the consumed media and hopes to encourage inclusion for disabled people accompanied by a change in the portrayal of disability identity in Malaysia.